The resonant images of the multitude: Egypt, Spain and Brazil | A ressonância das imagens da multidão: Egito, Espanha e Brasil - Freitas, Kênia (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
This article examines the resonant images produced by the emergent multitude in street demonstrations in Egypt, Spain and Brazil, between 2011 and 2013. The starting point for this work is the resonant nature of these moving images, understanding this resonance as a bodily, affective, tangible effervescence generated by the encounter of the multitude in political demonstrations. Thus, the aim of this work is to undertake a reflective analysis of the moving images of recent street protests through the quality of resonance contained within them. The hypothesis is that the resonant images of these insurgencies are elements of mobilization, memory and affective constitutiveness of these events.